Overexpression of miR-125a in myelodysplastic syndrome CD34+ cells modulates NF-κB activation and enhances erythroid differentiation arrest. - Irene Gañán-Gómez; Yue Wei; Hui Yang; Sherry Pierce; Carlos Bueso-Ramos; George Calin; George Calin; María Del Carmen Boyano-Adánez; Guillermo García-Manero (PLoS ONE)
Myelodysplastic syndromes (MDS) are characterized by impaired proliferation and differentiation of hematopoietic stem cells. The participation of toll-like receptor (TLR)-mediated signaling in MDS is well documented. Increased TLR signaling leads to the constitutive activation of NF-κB, which mediates inflammation, cell proliferation and apoptosis. In addition, the TLR pathway induces the expression of miRNAs which participate in the fine-tuning of the inflammatory response. miRNAs also regulate other biological processes, including hematopoiesis. miR-125a and miR-125b are known modulators of hematopoiesis and are abnormally expressed in several hematologic malignancies. However, little is known about their role in MDS. NF-κB-activating ability has been described for both miRNAs. We studied the role of miR-125a/miR-125b in MDS and their relationship with TLR signaling and hematopoietic differentiation. Our results indicate that miR-125a is significantly overexpressed in MDS patients and correlates negatively with patient survival. Expression of miR-99b, which is clustered with miR-125a, is also directly correlated with prognosis of MDS. Both miR-125a and miR-99b activated NF-κB in vitro; however, we observed a negative correlation between miR-99b expression and the levels of TLR2, TLR7 and two downstream genes, suggesting that NF-κB activation by the miRNA cluster occurs in the absence of TLR signaling. We also show that TLR7 is negatively correlated with patient survival in MDS. In addition, our data suggest that miR-125a may act as an NF-κB inhibitor upon TLR stimulation. These results indicate that miR-125a is involved in the fine-tuning of NF-κB activity and that its effects may depend on the status of the TLR pathway. Furthermore, we observed that miR-125a inhibits erythroid differentiation in leukemia and MDS cell lines. Therefore, this miRNA could serve as a prognostic marker and a potential therapeutic target in MDS.